Development Of The Anem Sip Education Model For Anemia Prevention In Adolescent Girls - Siregar, Sarinah; Johari, Asni; Syahrial, Syahrial; Huda, Nizlel (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Anemia remains a common health issue among women aged 15–48 years, with a global prevalence of 30% and 18% in Indonesia. Various educational methods have been employed, yet the demand for Android-based educational models remains high. This study aimed to develop and evaluate the effectiveness of the Anem SIP educational model for anemia prevention in adolescent girls, using a mixed methods approach and the ADDIE development model. The study adopted a mixed methods approach with the ADDIE development framework. The product was developed through validation by four experts, followed by one-on-one testing, small group testing, and field trials. The needs assessment stage served as the foundational step in the development process. Interviews with stakeholders and a survey of 30 adolescent girls indicated a continued need for an Android-based educational model. The model was designed based on the Health Belief Model (HBM), supported by the PRECEDE-PROCEED model, Social Cognitive Theory (SCT), Transtheoretical Model (TTM), multimedia learning, and the Technology Acceptance Model (TAM). The final product was the Anem SIP mobile application, featuring promotive, preventive, diagnostic, and monitoring components for iron-folic acid (IFA) supplement intake. Validation by four experts confirmed the model’s feasibility, and testing showed it to be user-friendly. The model comprises six procedural stages: problem identification, initial evaluation, preparation, action, final evaluation, and maintenance. Field testing revealed significant improvements in knowledge, attitudes, and adherence to IFA supplement consumption before and after the intervention. The t-test showed statistically significant increases in knowledge and attitudes (p < 0.001). Laboratory examinations also indicated an increase in average hemoglobin levels post-intervention. The Anem SIP intervention demonstrates promising potential in enhancing knowledge, attitudes, and behavioral changes among adolescent girls for the prevention of anemia